Photocatalytic Reduction of Cr(VI) from Aqueous Solutions with Formic Acid in the Presence of Bauxite: Kinetics and Mechanism - Arslanoglu, Hasan; Altundogan, H. Soner; Tumen, Fikret (Springer India, 2021)
Cr(VI) is one of the most dangerous heavy metal pollutants in the industrial wastewaters. It is very difficult to remove the Cr(VI) by direct precipitation and it is needed to be reduced to Cr(III) form in order to remove by conventional precipitation methods. The materials used in Cr(VI) reduction are SO2 and its derivatives, Fe(II) salts and metallic iron. The reduction of Cr(VI)-Cr(III) is able to be achieved by a photocatalytic process. In this study, photocatalytic reduction of Cr(VI) in formic acid-bauxite system under irradiation by a medium-pressure mercury lamp (UV/visible) was investigated. Photocatalytic reduction of Cr(VI) over bauxite catalysts was investigated in both the absence and the presence of formic acid. Effects of initial pH value and formic acid initial concentration on Cr(VI) photocatalytic reduction were studied. The results indicate that formic acid-bauxite system is able to rapidly and effectively photocatalytically reduce Cr(VI) utilizing UV light. Initial pH variations are resulted in the changes of formic acid-bauxite in this system, and pH at 3.0 is optimal for Cr(VI) photocatalytic reduction. Kinetics analysis indicates that initial sulfuric acid and formic acid concentrations affects Cr(VI) photoreduction most significantly. [GRAPHICS] .
Keywords: Photocatalyic reduction; UV; Cr(VI) reduction; Bauxite; Formic acid